THE THRESHOLD OF HIGH TECHNOLOGY IN GLOBAL COMMERCE: LEVERAGING THE ROLE OF HIGHER EDUCATION INSTITUTION - Ruswiati, Ruswiati (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2019)
Global commerce is a transborder movement that is giving rise to varied alternative providers and services that cut through traditional structures to the international context in the era of technological disruption. As the legitimate providers of commerce-allied disciplines, Higher education institutions assume a compelling role to survive and move into the loop of intensive technology adaption to bring across transnational transactions for which cross-border commerce, global regulation, and legitimization of activities are the emerging points of multi-national convergence. This paper seeks to reflect about the purpose and the point of convergence between traditional commerce and global commerce and the emergent strategies in response to the relentless shockwaves of globalization and technological advancement, making the role of higher education sector more dynamically compelling and responsive.